Catalytic hydrogen adsorption of nano-crystalline hydrotalcite derived mixed oxides - Salam, M.A. (2013)
Nano-crytalline hydrotalcite derived reduced mixed oxides containing magnesium, nickel and aluminium (MNAM) have been synthesized using coprecipitation and showed successfully nickel catalysed reversible hydrogen adsorption using the temperature programmed technique under near ambient conditions. ICP-MS and XRD analysis ensured the adsorbent homogeneity and different crystalline phases of mixed oxides. Morphology and textural properties of mixed oxides have been explored using the FESEM, BET and HRTEM analysis techniques. Nano-crystalline and mesporous reduced mixed oxides exhibited a 3.9wt H2 adsorption capacity in where desorption capacity was 1.9wt H2. Hydrogen adsorbed surface and different phases were analysed by XPS, Raman and FTIR analysis techniques. The hydrogen adsorption enthalpy (Î´H) and entropy (Î´S) changes of reduced mixed oxides were -47.58kJ/mol and -120.98J/molK, respectively, and the promising desorption activation energy of 65kJ/mol correspond its reversibility as potential energy storage material. Â© 2013 The Institution of Chemical Engineers.